Quality Improvement of Athletic Learning in Junior High School Through Modification of Learning - Riyadi, Slamet (Sebelas Maret University, 2016)
Physical education is part of a complete education, which has a strategic role to educate. The final goal ofphysical education and health sports (penjasorkes) lies in its role as a medium of refinement of character Â and personality form. Changes in behavior of learners, will be achieved through the learning process. Inorder to achieve good learning outcomes, teacher penjasorkes need to seek active learning, innovative,creative and fun.This paper aims to give an idea of the importance of improving the quality of learning throughmodifications in penjasorkes athletic. Modification of learning is one of the efforts to improve the qualityof penjasorkes learning. Modifications can be done in a modified form of infrastructure, materials andmethods. Modification approach in the form of a method may include play activities and competitions.Learning with a modified approach may be one alternative to creating a fun learning.